Speech as Noise Interference During a Mass Event. Issue 4 (March 2021) - Shubin, I L; Antonov, A I; Ledenev, V I; Yarovaya, T S
Abstract: Participants of mass events are noise sources for surrounding area and perception of information. To rate the intelligibility of the signals of sound amplification systems and to design the instruments of the noise insolation, the methods of calculating the propagation of sound energy from distributed noise sources such as people are developed. Methods take into account features of the emission of sound energy by such sources. The features include time-varying acoustic and spatial characteristics of noise sources. They are associated with the random nature of the position and direction of noise emission from event visitors. The method of calculating the energy parameters of direct sound depends on the parameters of the noise source. The low density of people location implies to use the method of mathematical modeling, including the random position, orientation and duration of speech of noise sources. The increase in the mass character of events and the increase in the density of point noise sources are rational to use the integral calculation method. The numerical solution of the integral equation is implemented in a computer program and used for calculating the noise from fans of a football match at the stadium and adjacent urban development. The methods for calculating direct sound from distributed sources in the form of a circle, a circular sector and a rectangle are suggested on the basis of an analytical solution of integral expressions. Comparison of calculation results by developed methods and experimental data is performed. The discrepancy between the results in the most difficult situations doesn't exceed ± 3 dB.